Maximal expiratory pressure and Valsalva manoeuvre do not produce similar cardiovascular responses in healthy men. Issue 5 (1st May 2016) - Minatel, Vinicius; Takahashi, Anielle C. M.; Perseguini, Natália Maria; Milan, Juliana Cristina; Castello‐Simões, Viviane; Gomes, Ellen C.; Borghi‐Silva, Audrey; Catai, Aparecida Maria
Abstract : New Findings: What is the central question of this study? This is the first study to evaluate and describe the cardiovascular responses during maximal expiratory pressure compared with the Valsalva manoeuvre, and whether those responses are similar. What is the main finding and its importance? This study showed that the duration of the manoeuvres appears to be responsible for the different physiological mechanisms involved in the cardiovascular responses to each manoeuvre and that the intensity of expiratory effort was related to the response in maximal expiratory pressure. These results are important to identify the risks to which subjects are exposed when performing these manoeuvres. The main purpose of this study was to compare the cardiovascular responses between the Valsalva manoeuvre (VM) and maximal expiratory pressure (MEP) and to evaluate the effect of age on these responses. Twenty‐eight healthy men were evaluated and divided into two groups, younger ( n  = 15, 25 ± 5 years) and middle aged ( n  = 13, 50 ± 5 years), and they performed the VM and MEP measurement. The VM consisted of an expiratory effort (40 mmHg) against a manometer for 15 s, and the MEP was performed according to American Thoracic Society guidelines. The cardiovascular responses were analysed at rest, isotime (3 s), peak, nadir and recovery, and the cardiovascular variations (Δ) were calculated as peak or isotime minus resting values. For the statistical analysis, we used two‐way ANOVA ( P  < 0.05). We observed that MEP and the VM generate similar changes in cardiac output ( P  > 0.05), but MEP presents higher values for mean arterial pressure (MAPPeak, MAPIsotime, ΔMAP and ΔMAPIsotime ) than those observed in the VM ( P  < 0.05). The execution time of the manoeuvres (VM ∼15 s and MEP ∼5 s) appears to be largely responsible for the activation of different physiological mechanisms involved in the cardiovascular control for each manoeuvre, and the intensity of expiratory effort is related to the higher response of MAP and peripheral vascular resistance (PVRIsotime and ΔPVRIsotime ) during MEP ( P  < 0.05). Moreover, it appears that age affects only the heart rate and PVR responses ( P  < 0.05), which were higher in the young and middle‐aged group, respectively. Based on these findings, we can conclude that MEP and the VM do not generate similar cardiovascular responses, except for cardiac output. Abstract :